Pollen colour morphs take different paths to fitness. (18th February 2020) - Koski, Matthew H.; Berardi, Andrea E.; Galloway, Laura F.
Abstract: Colour phenotypes are often involved in communication and are thus under selection by species interactions. However, selection may also act on colour through correlated traits or alternative functions of biochemical pigments. Such forms of selection are instrumental in maintaining petal colour diversity in plants. Pollen colour also varies markedly, but the maintenance of this variation is little understood. In Campanula americana, pollen ranges from white to dark purple, with darker morphs garnering more pollinator visits and exhibiting elevated pollen performance under heat stress. Here, we generate an F2 population segregating for pollen colour and measure correlations with floral traits, pollen attributes and plant‐level traits related to fitness. We determine the pigment biochemistry of colour variants and evaluate maternal and paternal fitness of light and dark morphs by crossing within and between morphs. Pollen colour was largely uncorrelated with floral traits (petal colour, size, nectar traits) suggesting it can evolve independently. Darker pollen grains were larger and had higher anthocyanin content (cyanidin and peonidin) which may explain why they outperform light pollen under heat stress. Overall, pollen‐related fitness metrics were greater for dark pollen, and dark pollen sires generated seeds with higher germination potential. Conversely, light pollen plants produce 61% more flowers than dark, and 18% more seeds per fruit, suggesting a seed production advantage. Results indicate that light and dark morphs may achieve fitness through different means—dark morphs appear to have a pollen advantage whereas light morphs have an ovule advantage—helping to explain the maintenance of pollen colour variation. Abstract : Extensive pollen color variation in Campanula americana is associated with pollen performance and seed production.